2016
DOI: 10.20537/nd1601008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic chaos in self-oscillating systems based on mechanical triple linkage: Testing absence of tangencies of stable and unstable manifolds for phase trajectories

Abstract: Сформулированы уравнения и проведено численное исследование хаотических автоколебаний в системах, построенных на основе тройного шарнирного механизма Тёрстона-Уикса-Ханта-Маккея. Рассмотрены варианты систем с голономной механической связью трех ротаторов и систем, где три ротатора взаимодействуют посредством потенциальных сил. Представлены и обсуждаются характеристики хаотических режимов (показатели Ляпунова, спектры мощности). Хаотическая динамика исследованных моделей ассоциируется с гиперболическим аттракто… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It means that we could also detect this situation taking the unit matrix as a metric and using the standard dot product instead of Eq. (35). However the angles computed in this way would depend on the discretization step h. The inner product (35) provides a correct asymptotic behavior of the angles as h → 0 when the numerical scheme converges to the original differential equations.…”
Section: Numerical Approximation Of the Adjoint Variational Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It means that we could also detect this situation taking the unit matrix as a metric and using the standard dot product instead of Eq. (35). However the angles computed in this way would depend on the discretization step h. The inner product (35) provides a correct asymptotic behavior of the angles as h → 0 when the numerical scheme converges to the original differential equations.…”
Section: Numerical Approximation Of the Adjoint Variational Equationsmentioning
confidence: 99%
“…(35). However the angles computed in this way would depend on the discretization step h. The inner product (35) provides a correct asymptotic behavior of the angles as h → 0 when the numerical scheme converges to the original differential equations. This is the case because Eq.…”
Section: Numerical Approximation Of the Adjoint Variational Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hunt and MacKay showed that the free motion of this mechanism with proper selection of parameters provides a feasible example of the Anosov flow on compact two-dimensional manifold of negative curvature [9]. The special case, when the constraint equation is simplified (in certain asymptotics in parameters) and reduces to a condition of vanishing sum of cosines of the three angles of revolution of the rotators about their fixed axes, was discussed in detail in [10,11]. The configuration space in this case is a two-dimensional curved surface, known as the Schwarz P-surface [12].…”
mentioning
confidence: 99%
“…This method was suggested initially in Ref. [11] and then developed and used with modifications in [12][13][14][15][16][17][18][19][20][21][22]. It may be regarded as an extended version of Lyapunov analyses, well-established and applied successively not only for low-dimensional systems but for spatiotemporal systems too.…”
mentioning
confidence: 99%